The types of left ventricular remodeling in patients with rheumatoid arthritis - I. A. Krivotulova; K. V. Korochina; T. V. Chernysheva; G. E. Kuznetsov; L. R. Tenchurina (Современная ревматология, 2020)
Studying the factors leading to a pathological change in the cardiac structure in patients with rheumatoid arthritis (RA) can contribute to improvement in early diagnosis and to prevention of premature mortality from cardiovascular events.Objective. To study the types of left ventricular (LV) remodeling in patients with RA, by taking into account traditional cardiovascular risk factors, and to assess the clinical and immunological features of RA and the impact of drug therapy.Patients and methods. The investigation enrolled 74 RA patients who underwent assessment of echocardiography findings, by determining the type of LV remodeling, traditional cardiovascular risk factors, clinical and immunological features of the disease, as well as the current drug therapy.Results and discussion. Eccentric LV hypertrophy (ELVH) (n=33 (44.59%)) and concentric LV hypertrophy (CLVH) (n=34 (45.95%)) occurred at almost the same frequency among the pathological types of LV remodeling in patients with RA. Higher DAS28 values (p<0.0001) were noted in ELVH than in CLVH. There were also positive correlations of EHLH with ESR and CRP level (r= 0.51, p<0.0001; r=0.48, p=0.0001, respectively). The higher values of systolic blood pressure (p=0.0002), body mass index (p=0.01), patient age (p=0.0001), and the incidence of dyslipidemia (p= 0.008) were established in CVLH than in ELVH. LV diastolic dysfunction (DD) was detected much more frequently in RA patients with CLVH than in those with ELVH (p=0.01). The DD parameters (peak A, E/A) correlated with the degree (r=0.5, p<0.0001; r=-0.5. p<0.0001) and stage of hypertension (r=0.54, p<0.0001; r=-0.48, p=0.0001, respectively), as well as with peak A and traditional risk factors, such as patient age (r=0.52, p<0.0001), and high-density lipoprotein cholesterol levels (r=-0.48, p=0.0001).Conclusion. Most patients with RA had signs of LV hypertrophy; moreover, ELVH was closely linked with disease activity, whereas CLVH was related to the traditional risk factors.